Genetic Structure of Maryland Brook Trout Populations: Management Implications for a Threatened Species. (28th June 2021) - Morgan, Raymond P.; Kazyak, David C.; King, Tim L.; Lubinski, Barbara A.; Sell, Matthew T.; Heft, Alan A.; Jones, Jess W.
Abstract: Brook Trout Salvelinus fontinalis have declined across their native range due to multiple anthropogenic factors, including landscape alteration and climate change. Although coldwater streams in Maryland (eastern United States) historically supported significant Brook Trout populations, only fragmented remnant populations remain, with the exception of the upper Savage River watershed in western Maryland. Using microsatellite data from 38 collections, we defined genetic relationships of Brook Trout populations in Maryland drainages. Microsatellite analyses of Brook Trout indicated the presence of five major discrete units defined as the Youghiogheny (Ohio), Susquehanna, Patapsco/Gunpowder, Catoctin, and Upper Potomac, with a distinct genetic subunit present in the Savage River (upper Potomac). We did not observe evidence for widespread hatchery introgression with native Brook Trout. However, genetic effects due to fragmentation were evident in several Maryland Brook Trout populations, resulting in erosion of diversity that may have negative implications for their future persistence. Our current study supplements an increasing body of evidence that Brook Trout populations in Maryland are highly susceptible to multiple anthropogenic stresses, and many populations may be extirpated in the near future. Future management efforts focused on habitat protection and potential stream restoration, coupled with a comprehensive assessment framework that includes genetic considerations, may provide the best outlook for Brook Trout populations in Maryland.